Ucp2-dependent microglia-neuronal coupling controls ventral hippocampal circuit function and anxiety-like behavior - Yasumoto, Yuki; Stoiljkovic, Milan; Kim, Jung Dae; Sestan-Pesa, Matija; Gao, Xiao-Bing; Diano, Sabrina; Horvath, Tamas L. (Molecular psychiatry, 2021)
Microglia have been implicated in synapse remodeling by phagocytosis of synaptic elements in the adult brain, but the mechanisms involved in the regulation of this process are ill-defined. By examining microglia-neuronal interaction in the ventral hippocampus, we found a significant reduction in spine synapse number during the light phase of the light/dark cycle accompanied by increased microglia-synapse contacts and an elevated amount of microglial phagocytic inclusions. This was followed by a transient rise in microglial production of reactive oxygen species (ROS) and a concurrent increase in expression of uncoupling protein 2 ( Ucp2 ), a regulator of mitochondrial ROS generation. Conditional ablation of Ucp2 from microglia hindered phasic elimination of spine synapses with consequent accumulations of ROS and lysosome-lipid droplet complexes, which resulted in hippocampal neuronal circuit dysfunctions assessed by electrophysiology, and altered anxiety-like behavior. These observations unmasked a novel and chronotypical interaction between microglia and neurons involved in the control of brain functions.